Call me by your name [videorecording (DVD)] - Hammer, Armie, 1986-; Chalamet, Timothée; Stuhlbarg, Michael; Aciman, André (Sony Pictures Classics, 2018)
It's the summer of 1983 in Italy, and Elio, a precocious 17-year-old, spends his days in his family's villa transcribing and playing classical music, reading and flirting with his friend Marzia. One day, Oliver, a charming American scholar arrives as the annual summer intern tasked with helping Elio's father, an eminent professor. Elio and Oliver discover the heady beauty of awakening desire over the course of a summer that will alter their lives forever.